Constructed Wetlands for Wastewater Treatment - Malabika Biswas Roy; Shilpa Saha; Pankaj Kumar Roy (Ecology, Economy and Society – The INSEE Journal)
Constructed wetlands (CWs) mimic natural wetland processes and are designed primarily for wastewater treatment. Their cost-effectiveness and energy efficiency have made them popular globally. In the present study, the online Scopus database was used to identify 4407 documents related to CWs from 1991 to 2020 and bibliometric analysis was conducted. Among these, 209 publications were highly cited (>100 times), constituting 5.1% of all publications. VOSviewer software was used to conduct citation network analyses, which revealed a steady increase in annual publications on the topic over time. The United States, China, and the Czech Republic produced the highest number of highly cited publications. Notably, the journal Ecological Engineering received the most citations, followed by Water Research and Water Science and Technology. The literature analysis explored CW design, the role of macrophytes and microorganisms, organic pollutant and nutrient removal processes, and operation and maintenance. Typha latifolia and Phragmites australis are commonly used plant species in CWs. Despite their efficacy and cost-efficiency, challenges such as difficulties in procuring land, conducting regular maintenance, and raising public awareness persist. Further research and innovation are crucial for maximizing CW applications in wastewater treatment in the modern era.